PENERAPAN METODE COOPERATIVE LEARNING TIPE GROUP INVESTIGATION UNTUK MENINGKATKAN KEAKTIFAN BELAJAR DAN HASIL BELAJAR IPA PADA SISWA KELAS V DI SDN 006 BANGUN PURBA - Nutun Nutun (JURNAL PENDIDIKAN ROKANIA, 2019)
This study aims to improve student learning outcomes and activeness in science subjects at SDN 006 Bangun Purba using cooperative learning methods of group investigation type. This type of research is action research or action research. The instruments used were observation sheets and performance tests. The results showed an increase in student learning activeness as evidenced by the student activity score from pre-cycle of 58.62%, then the first cycle of 68.97%, and Cycle II of 82.25%. Furthermore, an increase in student learning outcomes, namely pre-cycle students who completed as many as 7 students (48.28%) and an average of 64. In the first cycle there was an increase in the number of students who completed learning by 10 students (72.41%) and the average average reached 69, then in cycle II completed learning 14 students (100%) with an average of 75. It was concluded that the cooperative learning method of the type of investigation group could increase the activity of learning and student learning outcomes in science subjects.